Answers

2016-02-18T23:55:21+05:30
(17 (2 (-9)-3 (17-1))รท2
0
2016-02-19T00:24:21+05:30
Sum of 17 terms = (a1 + a17)*17/2.

Need to find first term & common difference.

a4 = -15
a + 3d = -15

a9 = -30
a + 8d = -30

Solving it, 5d = -15, d=-3//
Therefore, a = -6

Therefore a17 = a + 16d = -6 - 48 = -54

Therefore, sum of first 17 terms = (-6 -54)*17/2 = -510//
0
If u r happy with the answer, pls mark as Brainliest. Thank you!
oh yeah....thanks Vee1 i guess my mistake was the value of my "a" instead of (-6) I wrote (-9)..... thnx a lot.... sorry guys that's my bad